Pemandu Museum di Era Digital: Perlukah? - Inas Amatullah El Wachidah; Salma Fitri Kusumastuti (Jambura History and Culture Journal, 2026)
Digital transformation has driven museums to incorporate diverse interpretive media, including QR codes, audioguides, and immersive technologies, renewing questions about the contemporary relevance of museum guides. This article examines the role of guides in the digital era through participatory observation in three museums with distinct guiding systems: Lokananta (mandatory guided introduction), Museum Sonobudoyo (optional guidance), and Museum Ullen Sentalu (full guidance through Digital Free Tourism). Findings indicate that while digital technologies expand informational access and support autonomous exploration, they do not replicate the human interaction, narrative depth, and interpretive mediation provided by guides. Guides remain essential for managing visit rhythm, offering spatial orientation, and safeguarding collections. Visitor experience is further shaped by the guide’s competence and the potential for narrative bias. The study concludes that guides and digital technologies operate complementarily in contemporary museum practice, with their effectiveness contingent on each museum’s characteristics and interpretive needs.